O construcionismo contextualizado por meio da linguagem de programação Logo : uma proposta de ensino-aprendizagem da geometria plana - Biriba, Guilherme Barbosa (2023)
This research had as object of study the teaching and learning process of plane geometry mediated by the Logo programming language. The use of Digital Information and Communication Technologies (TDIC) as a mediator in the teaching and learning process, based on the idea of the learning spiral, allowed students to check and review the studied concepts. The central problem was delimited through a research question: how can the Logo programming language contribute to the construction of knowledge of elementary school students in the context of Constructionism? In order to find answers to this question, the research sought to investigate the impacts caused by the use of the Logo language in the flat geometry classes of the Mathematics discipline, having Constructionism as a theoretical basis. For the application of the experiment, the selected field of study was the Colégio de Administração at the Federal University of Sergipe (CODAP/UFS), with students from the 6th year of elementary school. Regarding the methodology, the research adopted a qualitative approach, focusing on data that cannot be measured by statistics. The type of research chosen was participant research, as the researcher was immersed in the study environment. The instruments and techniques used were questionnaires and the teacher's report, respectively, as a means of recording the construction of students' knowledge in relation to the concepts of plane geometry in the Mathematics discipline, inserted in the experience of using Logo. Data were analyzed using Discursive Textual Analysis, which highlighted the importance of Logo Language as a relevant pedagogical resource within a constructionist approach. The research made contributions, in the sense of bringing new teaching-learning strategies that privilege first-person learning supported by DICT and also provided enriching the training of future educators, improving educational practices, by integrating digital technology in the form of computer programming with a view to developing student autonomy and meaningful learning.